The Effect an Educational Program Using Cognitive Techniques to Developing Football Dribbling Skill for Students - Mustafa Jawad Mraidi; Hatham Hussein Abed (Institute of Medico-legal Publications Pvt Ltd, 2021)
The current study aimed to prepare an educational program using cognitive techniques and to get acquainted with it for second stage students in the College of Physical Education and Sports Sciences at Dhi Qar University for the academic year (2020-2021), and to identify the impact of the program on the performance of skill (dribbling) in football, and it has been the researchers hypothesized that the program had a positive effect on students’ performance.The researchers used the experimental approach in performance for the skill (dribbling) in football, and after dividing the sample into two groups (control and experimental) by (15 / students) for each group, the (control group) used the teaching method within the curriculum of the subject teacher, while the members of (experimental group) used the educational program using cognitive techniques, as for the field experiment, the tests procedures were conducted for (pre-test), after which the educational program was applied using cognitive techniques on individuals (the experimental group), where the number of educational units was (12 / unit), and then tests were conducted for (post-test), after that do statistical data processing.